468 Relationship Between Tumor Location and Quality and Extent of Resection in the Surgical Treatment of Myxopapillary Ependymoma. (April 2023) - Joiner, Evan F.; Greenwald, Phoebe; Neira, Justin Anthony; Kostadinov, Jane; Khandji, Alexander; Mandigo, Christopher Eliot; Angevine, Peter D.; McCormick, Paul C.
Abstract : INTRODUCTION: Myxopapillary ependymomas (MPE) are benign spinal tumors that present substantial heterogeneity with respect to size, location, and marginal integrity. These factors influence both extent and technique of tumor resection as well as the risk of tumor recurrence and CSF dissemination. METHODS: A retrospective review of all patients treated surgically for MPE at a tertiary care center from 1998 to 2021 was performed. RESULTS: Fifty-six patients (32 male, 24 female; age 21 to 77 years, mean 45.8 years) were included in the study. Sixty primary surgical procedures were performed (4 patients underwent a second surgery for removal of pre-existing sacral drop metastases). The quality and extent of resection was categorized as en bloc gross total resection (eGTR, n = 15), marginal GTR (mGTR, n = 17), piecemeal GTR (pGTR, n = 6), piecemeal near total resection (pNTR, n = 9), and subtotal resection (STR, n = 13). Fourteen of 15 eGTRs and all 17 mGTRs were accomplished in patients with tumors at or above L3. In contrast, 3/6 pGTRs, 5/9 pNTRs, and 10/13 STRs occurred in patients with tumors below L3 (p < 0.001 for Fisher's exact test). Tumor recurrence was noted in 1/15 patients who received eGTR, 1/17 who received mGTR, 0/6 who received pGTR, 1/9 who received pNTR, and 9/13 who received STR (p < 0.001). CONCLUSIONS: MPEs are heterogeneous neoplasms. The quality and extent of resection is often dictated by tumor location, which in turn correlates with the marginal integrity of the tumor. Tumors located below L3 are more often poorly marginated—allowing for only subtotal or piecemeal resection—while tumors at or above L3 are more likely to be amenable to eGTR or mGTR.